2014
DOI: 10.1093/mnras/stu1985
|View full text |Cite
|
Sign up to set email alerts
|

The formation of stellar nuclear discs in bar-induced gas inflows

Abstract: The role of gas in the mass assembly at the nuclei of galaxies is still subject to some uncertainty. Stellar nuclear discs bridge the gap between the large-scale galaxy and the central massive objects that reside there. Using a high resolution simulation of a galaxy forming out of gas cooling and settling into a disc, we study the formation and properties of nuclear discs. Gas, driven to the centre by a bar, settles into a rotating star-forming nuclear disc (ND). This ND is thinner, younger, kinematically cool… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(133 citation statements)
references
References 96 publications
(119 reference statements)
7
126
0
Order By: Relevance
“…For the RT calculation, we considered the model after 10 Gyr of evolution. At this epoch, Cole et al (2014) show that the model has a prominent nuclear disc while Ness et al (2014) show that the bulge has a range of stellar ages. The galaxy global parameters can be found in Table 1.…”
Section: The N-body+sph Galaxy Simulationmentioning
confidence: 98%
“…For the RT calculation, we considered the model after 10 Gyr of evolution. At this epoch, Cole et al (2014) show that the model has a prominent nuclear disc while Ness et al (2014) show that the bulge has a range of stellar ages. The galaxy global parameters can be found in Table 1.…”
Section: The N-body+sph Galaxy Simulationmentioning
confidence: 98%
“…The relatively high gas inflow rate to the centre of the model, with the attendant angular momentum transport and high star formation rate, is probably the source of this slow growth. Cole et al (2014) showed that this gas inflow produces a nuclear disc, which Debattista et al (2015) proposed is the origin of the high-velocity peaks seen in the mid-plane line-of-sight velocity distributions at l 6 • − 8 • in the APOGEE data (Nidever et al 2012). (Alternatively Aumer & Schönrich 2015, proposed that these high-velocity peaks are produced by young stars trapped by the bar from the disc.…”
Section: Caveats About the Modelmentioning
confidence: 99%
“…We consider the evolution of the model presented by Cole et al (2014) and Ness et al (2014). Briefly, in this simulation, a disc galaxy forms entirely out of gas cooling from a spherical corona and settling into a disc, triggering continuous star formation.…”
Section: Simulation With Star Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Combes & Gerin 1985;Athanassoula 1992bAthanassoula , 2005Sellwood & Wilkinson 1993;Piner et al 1995;Sakamoto et al 1999;Rautiainen & Salo 2000;Regan & Teuben 2003Sheth et al 2005;Wozniak 2007;Knapen 2007;Gadotti 2009;Kim et al 2012;Cole et al 2014;Emsellem et al 2015;Sormani et al 2015, and references therein). The inflow of gas may trigger inner discs and/or nuclear rings comprised of recently formed stars, at or near the inner Lindblad resonance (ILR) associated with the bar or rather at the region dominated by the bar × 2 orbits.…”
Section: Introductionmentioning
confidence: 99%